2010
DOI: 10.1089/jmf.2010.1074
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Alters Lipid Profiles, Total Antioxidant Capacity, and Vitamins A, E, and C Concentrations in Humans

Abstract: Although hemodialysis (HD) is essential for end-stage renal disease patients, at the same time it causes oxidative stress and long-term pro-atherosclerotic effects. This study aimed to determine lipid profile as well as the total antioxidant capacity (TAC) and vitamins A, E, and C in HD patients. The study enrolled 31 patients (50.3 ± 14.9 years old) undergoing maintenance 4-hour HD three times per week with a polysulfone membrane dialyzer for a mean of 76.1 months (range, 7-120 months) and 31 healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
6
16
0
Order By: Relevance
“…PAB assay using simple and rapid tests can help to identify patients at risk and prevent or reduce of complications resulting from oxidative stress. In our previous studies [6,20], we indicated a defective antioxidant defense during the process of HD, due to the reduction of antioxidants and elevated lipid peroxidation in patients on HD in agreement with the other studies [7,9,[12][13][14]21]. However, a study has shown decrease in the serum levels of MDA compared to control group [22].…”
Section: Discussionsupporting
confidence: 90%
“…PAB assay using simple and rapid tests can help to identify patients at risk and prevent or reduce of complications resulting from oxidative stress. In our previous studies [6,20], we indicated a defective antioxidant defense during the process of HD, due to the reduction of antioxidants and elevated lipid peroxidation in patients on HD in agreement with the other studies [7,9,[12][13][14]21]. However, a study has shown decrease in the serum levels of MDA compared to control group [22].…”
Section: Discussionsupporting
confidence: 90%
“…Renal dietary restrictions imposed on such patients make it more likely they will avoid foods with high vitamin C content. Additionally, vitamin C is cleared during standard hemodialysis sessions [47][48][49] . However, vitamin C supplementation contributes to a rise in oxalate 47 which can deposit in tissues and lead to bone disease, arthropathies, vascular calcification, skin deposits, and liver failure 50 .…”
Section: Evidence For Altered Requirements In Hemodialysis Patientsmentioning
confidence: 99%
“…14,15 Erythrocyte SOD and GPx activity were measured using commercial colorimetric assay kit (Randox, Crumlin, County Antrim, UK) as described previously. 11,15 Serum vitamin A and E were extracted with hexane and measured by using high pressure liquid chromatography with absorption at 325 nm and 292 nm, respectively.…”
Section: Antioxidants Assaymentioning
confidence: 99%